Quantifying the relationship between quadriceps strength and aerobic fitness following anterior cruciate ligament reconstruction. (May 2022) - Slater, Lindsay V.; Hart, Joseph M.
Abstract: Objective: To quantify the relationship between quadriceps strength and aerobic fitness following ACLR. Methods: 42 individuals with ACLR (29F/13M, 20.2 ± 3.3years, 71.8 ± 17.4 kg, 171.1 ± 9.4 cm, 21.9 ± 21.5months post-surgery) and 38 healthy controls (24F/14M, 20.1 ± 1.4years, 69.8 ± 10.2 kg, 172.9 ± 8.7 cm) completed quadriceps strength testing using an instrumented dynamometer then completed an incremental treadmill test to determine aerobic fitness (VO2 max). Bivariate Pearson's correlations were calculated between strength and VO2 max. Significant correlations were retained for a regression analysis. Results: Healthy controls demonstrated significantly greater VO2 max compared to the ACLR group ( d  = 0.56). Unilateral strength variables were significantly correlated with VO2 max (P ≤ 0.006) for both groups. Normalized peak isokinetic knee extensor torque was retained in the model, which explained 20.5% of the variance in healthy VO2 max and 37.2% of the variance in ACLR VO2 max. Conclusions: Aerobic fitness was reduced in the ACLR group in comparison to the healthy controls, despite unrestricted return to activity and similar activity levels between groups. Unilateral quadriceps strength was significantly correlated with aerobic fitness, which may be an indicator that greater unilateral strength may be a proxy for assessing aerobic fitness. Furthermore, sports medicine professionals may consider incorporating techniques and exercises during rehabilitation to improve cardiovascular fitness following ACLR. Highlights: ACLR had reduced aerobic fitness despite unrestricted return to activity. Unilateral quadriceps strength was significantly correlated with aerobic fitness. Isokinetic quadriceps torque explained 37.2% of variance in ACLR aerobic fitness.